Implementations of the Cryocalorimeter facilities into the 121 TOF Mass Spectrometer; DKV-Tagungsbericht 2002, Magdeburg, 20- 22 November 2002; Arbeitsabteilung I, Band I - Uchaykin (Uchaikin) S. V. Sergey Victorovich; Christ P.; Probst F.; Rutzinger S.; Seidel W.; Stark M. (2002, 2002)
В фонде НТБ ТПУ отсутствует